The Effect of Sustainability Report Disclosure on Firm Value - Kusharyanti, Kusharyanti; Simamora, Puput Melati (EQUITY, 2023)
This study investigates the impact of presence and extent of sustainability reporting on firm value. The sample used in this research is mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. We obtained data from mining sector companies that have published sustainability reports and annual reports. This research uses OLS regression for testing the impact of sustainability report disclosure on firm value. The results of the analysis show that the presence of a sustainability report affects firm value. However, the extent of sustainability report do not impact firm value. This study demonstrates that the existence of a sustainability report alone is enough to have an impact on company value and does not need a high score. This study advances the legitimacy hypothesis by providing further data on the significance of sustainability reports.